Influence of green manure (Leucaena leucocephala) dosages on eggplant (Solanum melongena) growth and yield across diverse soil types - Anggit Kurniawan; Titin Setyorini; Valensi Kautsar (Universitas Lancang Kuning, 2023)
Eggplant cultivation displays versatility across various soil types. However, nutrient depletion, a result of excessive chemical fertilizer utilization, presents a growing concern. The integration of green manure into agricultural practices, catering to diverse soil types, can remediate this nutrient loss. The purpose of this study was to investigate eggplant growth and yield responses to differing green manure quantities across varying soil types. Employing a factorial experimental method, this research was structured in a completely randomized design (CRD). Two independent variables were evaluated: green manure dosage, with three levels (30 g/plant (D1), 60 g/plant (D2), 90 g/plant (D3)), and soil type, also classified into three categories: Latosol (T1), Grumusol (T2), and Regosol (T3). Data interpretation was conducted using analysis of variance, followed by the Tukey test, each executed at α = 5% significance level. Outcomes indicated a notable interaction between green manure dosage and soil type concerning the leaf area and root fresh weight parameters. The optimal combination emerged as a 30 g/plant green manure dosage applied to Regosol soil type. Notably, individual treatments exerted divergent effects on eggplant growth parameters, though no significant impact on eggplant yield parameters was observed. This research underscores the interplay between green manure usage and soil type in cultivating eggplants, adding value to sustainable agricultural practices.